"Regulate me not": The regulatory failures of taxation: A tale from Greece. (27th September 2018) - Kottaridi, Constantina; Thomakos, Dimitrios
Abstract : This paper is a critical review of the problems of the Greek tax system. A well‐structured tax system promotes allocative efficiency and supports economic growth, whereas on the contrary current Greek reality translates to nontransparency, complexity, and tax corruption: all of them constitute regulatory failure. Using data, which refer to detailed tax information on certain years, starting in 2006 and ending in 2011, and data on the total back taxes owed to the Greek state, we highlight both the problems but more importantly the need to restructure the Greek tax system to finally promote economic growth and not crony capitalism.